Carta de Antonio R. Barceló a Roberto H. Todd - Barceló, Antonio R.; Todd, Antonio R. (My University, 1931)
Recomendación para una persona no mencionada.
Keywords: Barceló, Antonio R., 1868-1938; Blanco Sosa, Julián E., 1830-1905